Human heredity: Principles and issues - Michael R Cummings (West Publishing, 1993)
The book presents the principles of genetics and their application to humans. It is divided into 20 chapters. Chapters 1 through 6 cover the transmission of genetic traits. Chapters 7 through 14 cover gene action and the production of phenotype. And chapters 15 through 20 cover populations, behavior,evolution, and the social aspects of genetics